'Free and easy wandering': Agnes Martin and the limits of intercultural dialogue. Issue 2 (2nd July 2016) - Morley, Simon
Abstract : I examine the impact of East Asian ideas on the paintings and writings of the American artist Agnes Martin (1912–2004), arguing that her relationship to such ideas was complex and often contradictory – at least on the level of the discourse she herself erected around her painting. I argue that while in practice her paintings express a view of subjectivity that is more familiar and more valued within East Asian culture, in her theory Martin nevertheless remained bound by Western dualistic thinking. The difference between the discursive nature of her writings and the nature of her writings and thinking, and the modality of her paintings draws attention to a more general problematic: the relationship between, on the one hand, the hermeneutic mode of awareness in art, and, on the other hand, the non-discursive mode of awareness in art practice. I draw attention to the latter mode, which foregrounds corporeal expansions and extensions of the borders of the material body. The experience Martin sought to convey is based on unconscious, holistic intuition rather than on the conscious, reflexive presentation of information. But when it came to articulating her intentions linguistically in her texts, Martin often defaulted to deep-rooted notions coming from her background culture. This is not surprising, insofar as she was inevitably bound to a paradigm from which she could not entirely escape, one in which process and 'becoming' were denigrated and under-theorized.